Tolerance Reflected In Kazuo Ishiguro's Never Let Me Go (2005): A Sociological Approach - Ridwan Seplawan, Andre; , Dr. Phil. Dewi Chandraningrum, M. Ed (2016)
This research paper is about tolerance in Kazuo Ishiguro's Never Let Me Go novel (2005) which is analyzed using Sociological Approach. The objective of this study are to find out how the condition of tolerance to the human clones which have a feeling for life. In analyzing Never Let Me Go, the researcher uses qualitative method and sociological approach. The primary data of this research is Never Let Me Go novel by Kazuo Ishiguro. The secondary data are some selected references and material related to the study. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The researcher draws the conclusion in this research. There is no tolerance or deferral for life of human clones. Human clones were created to donate the organ of the body to the real human.